Countering corporate power through social control: what does a social licence offer? - Haines, Fiona (The British journal of criminology, 2022)
This paper interrogates the capacity for social control to act as a complement and alternative to the law in controlling corporate harm. Social control can manifest as demands that businesses obtain a social, not just a legal, licence to operate which can provide an avenue for communities to reject or shape company operations. Drawing on parallels with the ambiguities that hinder the criminalization of business conduct, this paper shows how the social licence can also be used to silence critical voices or justify harmful practices. This ambiguity hinges on struggles around what is or is not socially desirable, which can engender significant conflict. Whilst this conflict might be inevitable, even productive in reducing corporate harm, it can leave a debilitating social legacy